Effectiveness of Office Ergonomics in Relation to Employees Productivity at ABC Animal Clinic Tandang Sora: Basis for Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Poor posture is almost every office worker's health problem. It is due mainly to inadequateoffice equipment and a lack of awareness. One of the disorders that a lousy posture brings tothe table is back pain. It is primarily because of the nature of passive work. Stress and strainresulting from manual animal handling are among the most common conditions that adverselyaffect employees' health for Research purposes. The ABC Animal Clinic employeesassociated with demanding manual tasks may result in increased occupational injuries,worker fatigue, absenteeism, poor human performance, and decreased productivity. Theemployees of the ABC Animal Clinic have a collaborative approach to their work, which isexcellent for building a positive and productive work environment. By allowing each other tohelp with various tasks, they can work more efficiently and effectively, reducing stress andpreventing burnout. In addition to improving individual job satisfaction, when individualscooperate to achieve a common objective, they develop stronger relationships and a greatersense of trust and respect for one another. Overall, this kind of collaborative work culture canbe a significant asset for any organization, and it's great to see the employees of the ABCAnimal Clinic taking steps to support each other in their work.Findings revealed that the employees of ABC Animal Clinic perform a range of tasksefficiently, promote a good working environment, and prevent themselves from getting injured.Their types of equipment are always clean. However, the employees experience Unorganizedand uneasy reaching Equipment, Foul smell that affects their productivity, some animalpatients cannot avoid experiencing stress while being held, and some employees experienceawkward postures.The researchers analyzed collected data to establish utilization in creating ergonomicdevelopment to improve employees' productivity, which will help them increase their Morale,Motivation, and Performance. This can benefit both employees and the organization bydeveloping more Effective ergonomics.
Keywords: Business